SOLVING FIRE DEPARTMENT STATION LOCATION PROBLEM USING MODIFIED BINARY GENETIC ALGORITHM: A CASE STUDY OF SAMSUN IN TURKEY - Maci, Irfan (European Scientific Journal, ESJ, 2015)
Fire and traffic accident are the most common problem in our daily lives. Fire department location for the purpose of easy response and recovery is a significant problem today. The best location of a fire department station determines the rate of recovery of many injured people after traffic accident, fire outbreak, and so on. In this paper, we considered the best location of fire stations. In addition, we also considered where the station is setup. Surveying problem is modeled as a mixed integer programming. It is solved by modified binary genetic algorithm, coding with GAMS. Modified binary GA is different from known GA with respect to binary decision variables. Due to this problem, initial value of the objective function was obtained from known GA. Then finally, the best result was achieved from binary GA.